Unveiling 21st Century Skills and Chemistry Concepts in the Movie the Martian (2015) - Arbi, Anggun Purnomo; Prasetyo, Muhammad Andi Tanri (CV. Aksara Global, 2024)
In the modern era, 21st century skills and chemistry concepts become very crucial to face global challenges. This study aims to analyse the representation of 21st century skills and chemistry concepts in the film The Martian (2015). This research uses content analysis method with a qualitative approach. The findings show that the film depicts skills such as Problem-solving, collaboration, critical thinking, research skills, effective communication, technological literacy, and adaptability, as well as chemistry concepts such as chemical property/property of oxygen, green chemistry, electro chemistry, chemistry reaction, Stoichiometry, Radiochemistry, physical chemistry, Chemistry Reaction: Reduction-Oxidation reaction. The implications of this study underscore the potential of films as an effective learning medium for teaching scientific skills and concepts that are important in STEM education. It is recommended that educators utilise film as a tool in the learning process.